Self-Appraisal and Its Relationship to Organizational Commitment and Job Involvement - Lim, Soo Giap (1996)
This study sought to investigate factors influencing employee self-evaluated performance of Mara Institute of Technology in Perlis. Age, Gender, Job Experience, Organisational Commitment, Job Involvement are the independent variables under this study. The dependent variable is Employee Performance dimension. The instrument was pre-test for validity and reliability. The results yielded an internal consistency of Cronbach’s Alpha = 0.91 Descriptive Statistics, Pearson’s Correlation and Multiple Regression Analysis are used to investigate the relationship between Age, Gender, Job Experience, Organisational Commitment, Job Involvement with Employee Performance. The findings showed that there were significant and positive correlations between age, organisational commitment, job involvement and employee self evaluated performance. Multiple Regression Analysis has shown that 33.3% of the observed variability in employee self-evaluated performance could be explained by the five independent variables (age, gender, job experience, organisational commitment, job involvement). The best predictor of the employee self-evaluated performance was found to be job involvement.